Blood-brain barrier integrity and prevalence of intrathecal T helper 17.1 cells in Huntington´s disease - Birna Ásbjörnsdóttir; Christian Sandøe Musaeus; Marie N. N. Hellem; Tua Vinther-Jensen; Patrick Ejlerskov; Esben Budtz-Jørgensen; Filippa Liliendahl Qvist; Anja Hviid Simonsen; Lena Elisabeth Hjermind; Niels Henning Skotte; Marina Rode von Essen; Finn Sellebjerg; et al. (PLoS ONE, 2026)
Background Blood-brain barrier (BBB) involvement in the pathogenesis of Huntington´s disease (HD) is not well understood. We previously demonstrated increased prevalence of T Helper 17.1 (Th17.1) cells in the cerebrospinal fluid (CSF) of HD gene-expansion carriers (HDGECs), which might indicate a dysfunction in the BBB or the blood-CSF barrier (BCB) in HD. Objective The aim of this exploratory study is to investigate whether the CSF/plasma albumin quotient (Q-Alb) and CSF platelet-derived growth factor-β (PDGFR-β) can be used as biomarkers for BBB/BCB integrity in HD and if there is an association between Q-Alb and the prevalence of intrathecal Th17.1 cells in HDGECs. Methods A total of 145 HDGECs and controls were included in the Q-Alb analysis. Forty-four of these individuals underwent a second lumbar puncture after five years and were included in the analysis of changes in Q-Alb over time. CSF from 33 HDGECs and controls was analysed for Th17.1 cells and CSF from 100 HDGECs and controls was analysed for PDGFR-β. Results No significant difference for Q-Alb was found between the pre-motor manifest HDGECs, motor manifest HDGECs, and controls (p = 0.49). We found a significant increase in Q-Alb in HDGECs over the 5-year period (p = 0.014), but when compared with controls, no significant difference was found (p = 0.32). No significant association was found between Q-Alb and the prevalence of Th17.1 cells (p = 0.97) nor Q-Alb and PDGFR-β (p = 0.89) in HDGECs. Conclusion We found no evidence of increased BBB/BCB leakage of albumin in HDGECs compared to controls. Neither did we find signs of pericyte involvement as measured by PDGFR-β in HDGECs. These results suggest that overt BBB/BCB disruption may be limited in HDGECs. Future longitudinal studies should employ more sensitive methods like dynamic contrast-enhanced magnetic resonance imaging to evaluate region specific microleaks.